Komparasi Aplikasi Perangkat Lunak Sistem Klasifikasi Ddc: Athenaeum Light 8.5., Dfw Version 1.00, We - Wijaya Hardiyati (IAIN Ponorogo, 2011)
Librarian has many alternative to classify DDC (DeweyDecimal Classification) number. Not only use printed DDC, butnow DDC software to help identify DDC number is available. Onof them is Athenaeum Light 8.5., DFW (Dewey For Windows)Version 1.00, WebDewey 2.0, e-DDC (electronic-Dewey DecimalClassification) Edition 22. In this paper, it will roll out about how touse that software with it excess and deficiency.